Secure data processing with massive‐parallel SIMD matrix for embedded SoC in digital‐convergence mobile devices. Issue 1 (15th November 2016) - Kumaki, Takeshi; Koide, Tetsushi; Fujino, Takeshi
Abstract : This paper presents secure data processing with a massive‐parallel single‐instruction multiple‐data (SIMD) matrix for embedded system‐on‐chip (SoC) in digital‐convergence mobile devices. Recent mobile devices are required to use private‐information‐secure technology, such as cipher processing, to prevent the leakage of personal information. However, this adds to the device's required specifications, especially cipher implementation for fast processing, power consumption, low hardware cost, adaptability, and end‐user's operation for maintaining the safety condition. To satisfy these security‐related requirements, we propose the interleaved‐bitslice processing method, which combines two processing concepts (bitslice processing and interleaved processing), for novel parallel block cipher processing with five confidentiality modes on mobile processors. Furthermore, we adopt a massive‐parallel SIMD matrix processor (MX‐1) for interleaved‐bitslice processing to verify the effectiveness of parallel block cipher implementation. As the implementation target from the Federal Information Processing Standardization‐approved block ciphers, a data encryption standard (DES), triple‐DES, and Advanced Encryption Standard (AES) algorithms are selected. For the AES algorithm, which is mainly studied in this paper, the MX‐1 implementation has up to 93% fewer clock cycles per byte than other conventional mobile processors. Additionally, the MX‐1 results are almost constant for all confidentiality modes. The practical‐use energy efficiency of parallel block cipher processing with the evaluation board for MX‐1 was found to be about 4.8 times higher than that of a BeagleBoard‐xM, which is a single‐board computer and uses the ARM Cortex‐A8 mobile processor. Furthermore, to improve the operation of a single‐bit logical function, we propose the development of a multi‐bit logical library for interleaved‐bitslice cipher processing with MX‐1. Thus, the number of clock cycles is the smallest among those reported in other related‐studies. Consequently, interleaved‐bitslice block cipher processing with five confidentiality modes on MX‐1 is effective for the implementation of parallel block cipher processing for several digital‐convergence mobile devices. © 2016 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.